2005
DOI: 10.1073/pnas.0501218102
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transition of amyloid β-peptide

Abstract: The amyloid ␤-peptides (A␤s), containing 39 -43 residues, are the key protein components of amyloid deposits in Alzheimer's disease. To structurally characterize the dynamic behavior of A␤40, 12 independent long-time molecular dynamics (MD) simulations for a total of 850 ns were performed on both the wide-type peptide and its mutant in both aqueous solution and a biomembrane environment. In aqueous solution, an ␣-helix to ␤-sheet conformational transition for A␤40 was observed, and an entire unfolding process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
259
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(286 citation statements)
references
References 60 publications
(125 reference statements)
20
259
1
4
Order By: Relevance
“…Results of this study showed that a folded A (1-42) monomer, but not A (1-40) monomer, possesses a turn at G37-G38 stabilized by a hydrophobic interaction between V36 and V39 [94]. This turn structure is in agreement with the solution 1 One of the most extensive all-atom MD studies of helixto-coil conformational change in A (1-40) monomer was reported by Xu et al, who studied A (1-40) folding in both aqueous and membrane-like environments [96]. In an aqueous solution, A (1-40) trajectories showed an -helix -sheet and a -sheet random coil conformational change.…”
Section: Folding Of Full-length Asupporting
confidence: 57%
“…Results of this study showed that a folded A (1-42) monomer, but not A (1-40) monomer, possesses a turn at G37-G38 stabilized by a hydrophobic interaction between V36 and V39 [94]. This turn structure is in agreement with the solution 1 One of the most extensive all-atom MD studies of helixto-coil conformational change in A (1-40) monomer was reported by Xu et al, who studied A (1-40) folding in both aqueous and membrane-like environments [96]. In an aqueous solution, A (1-40) trajectories showed an -helix -sheet and a -sheet random coil conformational change.…”
Section: Folding Of Full-length Asupporting
confidence: 57%
“…All previous MD studies of Ab in membranes 17,18,27,36,[39][40][41] have consisted of only a single lipid type or an implicit model representing a membrane. In this work, however, we have explored numerous explicit model membranes, including the most complex lipid environments in which Ab has been simulated to date, rafts that correspond very closely to the lipid matrix that Ab encounters upon its production following c-secretase cleavage of APP.…”
Section: Discussionmentioning
confidence: 99%
“…In one instance (simulation GM1-CI-5), a hairpin formed involving residues Val24-Gly25 and Lys28-Gly29, connected by a turn involving Ser26-Asn27. Formation of b-strand structures near glycines within residues 24-37 has previously been proposed as an important factor in the overall conversion of Ab from a-helix to bstrand, 27 but emergence of such structures has never before been observed in simulations of membrane-bound Ab, indicating that this behavior is related to the presence of a suitable hydrogen-bond donor/acceptor environment, such as GM1 or POPE, as we observed above in the case of simulation PC/ PE-CH-3. This phenomenon is discussed in greater detail below.…”
Section: Secondary Structure Of Ab 40mentioning
confidence: 99%
“…This peptide is produced by the proteolytic cleavage of the amyloid precursor protein by the b-and c-secretases to predominantly form 40-42 amino acid peptides [4]. In its native soluble state, the peptide adopts both helical and random-coil conformations [5]. Assembly of Ab monomers leads to soluble aggregates, namely oligomers, presenting b-structure [6].…”
Section: Introductionmentioning
confidence: 99%